(3GNJUGQ TQM GdHfGfj Ydi NWHI CdajI GHf eGdcs - (3MeOhf Hf eMeO HfGfj Hf YHO GdSdGes
(3ChdgG (B:s
(3hHYO, ajbhd MeOhf Hf eMeO HfGfj Hf YHOGdSdGe deG cGf TQM NGdfG YHOGddg SjOj eMeO Hf eMeO Hf MeOhf HfGfj s
(3BNQgG (B:s
(3fhY ef CfhGY GdHOjY hgh MSf GdGfJgGA, dCf GdNJe HGdOYGA eYghO ddHdZGA cbhdg HbjJ HbGA GdOgQ hgPG OYGA ddHQjI TGed hgPG BNQ GdGNJUGQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B10 s
Keywords: (3GdfMhs